PENGARUHIMPLEMENTASIELECTRONIC MEDICAL RECORDTERDAHAP BEBAN KERJA PETUGAS FILING - Haerudin Haerudin; Hendra Rohman; Endang Susilowati (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2018)
Electronic Medical Record (EMR) began to be implemented at Bethesda Hospital since 2014 and implemented in 28 outpatient polyclinics. Prior to the implementation of Electronic Medical Record, the filing workload of ten people was divided into two shifts, seven person at morning shift and three person at day shift, but after the implementation was reduced, just 3 person needed. This study aims to identify the influence of Electronic Medical Record on the workload of filing officer. Descriptive research with quantitative approach using case control survey design. Data collection using questionnaires. The result of the research through work load measurement by NASA-TLX method shows that the dominant Performance (P) factor influences the workload of officers A, E, G, H and I significantly, with p = 0.0008. Conclusion, the implementation of Electronic Medical Record outpatient has a significant effect on workload of filing officer.